Implementation of the Punggur Smart House Program Shaping the Religious Character of School Children in Punggur Kecil Village - Nunung, Nunung; Imran, Imran; Astari, Zuri; Bistari, Bistari; Utami, Tri (Universitas Tanjungpura, 2025)
This study aims to analyze the implementation of the Punggur Cerdas Smart House program in shaping the religious character of school-age children in Punggur Kecil Village. The background of this study is based on the importance of religious character education as the foundation for shaping noble character in the younger generation amid the moral challenges of modern society. Rumah Pintar Punggur Cerdas, as a non-formal educational institution, has various programs such as the Al-Qur'an Education Park (TPA) for memorizing the Al-Qur'an, studies, Kampung Ramadhan Ceria Annajihin, and religious studies that play a role in shaping the religious character of children. This study uses a qualitative approach with a descriptive method. Data was obtained through observation, interviews, and documentation involving administrators and school-age children (7